1992
DOI: 10.1111/j.1752-7325.1992.tb02276.x
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Toothpastes with Lower than Conventional Fluoride Concentrations for Preschool‐aged Children

Abstract: Since 1945, when community water fluoridation was first implemented in the United States, not only has the procedure grown to cover more than half of the US population, but the development and use of other fluoride methods have expanded greatly. A concomitant, dramatic decrease has occurred in the caries prevalence of US school-aged children. Recent studies indicate, however, that the prevalence and, to a lesser extent, the intensity of dental fluorosis have increased in schoolchildren in both fluoridated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 41 publications
1
40
0
6
Order By: Relevance
“…The results of different estimations of the combined effect following the meta-analytic procedures with heterogeneous criteria, using the Dersimonian-Laird random effect model are shown in the metaview (7,8,14,17).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The results of different estimations of the combined effect following the meta-analytic procedures with heterogeneous criteria, using the Dersimonian-Laird random effect model are shown in the metaview (7,8,14,17).…”
Section: Meta-analysismentioning
confidence: 99%
“…There is concern about dental fluorosis related to the chronic intake of excessive quantities of fluoride in children under 6 years of age. Some authors have reported that the early use of fluoridated toothpastes in young children is a very important risk factor (13,17,22,33,34). Beside fluoride concentration, the duration and age of exposure are important factors in fluorosis prevalence (2).…”
Section: Introductionmentioning
confidence: 99%
“…Recent concerns about the prevalence of dental fluorosis [Pendrys and Stamm, 1990;Horowitz, 1992;Levy, 1993] suggest the need to develop low F rinses and dentifrices; however, it is important that such formulations maintain a high level of anticaries activity [Winter et al, 1989;Holt et al, 1994]. Low-F two-component rinses and perhaps dentifrices can be devised to address these concerns.…”
Section: Introductionmentioning
confidence: 99%
“…De fato, a interpretação dos resultados relativos aos estudos de fluorose dentária e suas implicações para a Saúde Coletiva têm desafiado os pesquisadores e os sanitaristas nas últi-mas duas décadas, especialmente em virtude da multiplicação das fontes de flúor, do risco potencial que isso tem representado para a ocorrência de fluorose e o efetivo aumento observado em sua prevalência em diversas partes do mundo, em regiões com e sem as águas de abastecimento fluoretadas 4,5,7,8,26 . Essa elevação tem sido atribuída basicamente à associação de métodos sistêmicos (água + medicamentos + polivitamínicos) e à ingestão de flúor a partir do uso inadequado de produtos tópi-cos, principalmente cremes dentais na primeira infância.…”
Section: Discussionunclassified
“…Alguns autores notaram maior aumento proporcional em locais com teores deficientes de flúor na água 4,5 ; outros observaram diferenças pequenas entre áreas fluoretadas e não fluoretadas 6,7 ; e outros, sem entrar no mérito do seu aumento, atribuíram a ocorrência das formas leves à fluoretação da água 8 .…”
Section: Introductionunclassified